Evaluation of automated erythrocyte methodology in new world camelids using the ADVIA 2120 hematology analyzer. (9th June 2019) - Viesselmann, Lisa C.; Flatland, Bente; Stokol, Tracy; Sisson, Sandra; Schaefer, Deanna M. W.
Abstract: Background: Accurate erythrocyte measurements with ADVIA hematology analyzers require isovolumetric cell sphering in one reaction and hemolysis in another. However, camelid erythrocytes are resistant to sphering and osmotic lysis, and no published evaluation of ADVIA methods for camelids exists. Objectives: The objectives were to demonstrate whether camelid erythrocytes sphere in the ADVIA red blood cell/platelet (RBC/PLT) reagent and lyse in the ADVIA cyanide HGB reagent, and to determine optimal ADVIA settings for camelids. Methods: Camelid and canine blood were diluted to 1:625 in RBC/PLT reagent and evaluated microscopically for erythrocyte sphering. A camelid sample was incubated with the hemoglobin (HGB) reagent at varying dilutions to evaluate hemolysis. The RBC, hematocrit (HCT), mean cell volume (MCV), and mean corpuscular hemoglobin concentration (MCHC) using three ADVIA species settings (equine, bovine, and caprine) were compared to their respective reference methods: Z2 Coulter impedance counter, packed cell volume, calculated MCV (PCV × 10/Coulter RBC), and calculated MCHC (HGB × 100/PCV). Reference MCV was also compared to MCV calculated using the ADVIA equine RBC count. Comparisons were assessed using Passing‐Bablok regression and Bland‐Altman difference plots. Results: Camelid erythrocytes did not sphere in the RBC/PLT reagent, but did lyse in the HGB reagent. The ADVIA equine setting RBC count was acceptably close to the Coulter count. Hematocrit, MCV, and MCHC from all settings were significantly different from the reference methods. Mean cell volumes calculated using the equine setting RBC counts were acceptably close to the reference MCV. Conclusions: Camelid ADVIA erythrogram results should be reported as follows: RBC counts and HGB concentrations using the equine setting, spun PCVs, MCVs calculated using the PCV and equine setting RBC, and MCHCs calculated using the PCV and equine setting HGB.